Structure and localization of genes encoding aberrant and normal epidermal growth factor receptor RNAs from A431 human carcinoma cells. - Merlino, G T (1985)
A431 cells have an amplification of the epidermal growth factor (EGF) receptor gene, the cellular homolog of the v-erb B oncogene, and overproduce an aberrant 2.9-kilobase RNA that encodes a portion of the EGF receptor. A cDNA (pE15) for the aberrant RNA was cloned, sequenced, and used to analyze genomic DNA blots from A431 and normal cells. These data indicate that the aberrant RNA is created by a gene rearrangement within chromosome 7, resulting in a fusion of the 5' portion of the EGF receptor gene to an unidentified region of genomic DNA. The unidentified sequences are amplified to about the same degree (20- to 30-fold) as the EGF receptor sequences. In situ hybridization to chromosomes from normal cells and A431 cells show that both the EGF receptor gene and the unidentified DNA are localized to the p14-p12 region of chromosome 7. By using cDNA fragments to probe DNA blots from mouse-A431 somatic cell hybrids, the rearranged receptor gene was shown to be associated with translocation chromosome M4.